O conceito de big data: novos desafios, novas oportunidades - Gutierres, Luna Neide Macedo (2017)
The world faces exponential data growth. Data is created by smart devices, RFID technologies (Radio-Frequency IDentification), sensors, social networks, video surveillance and more. These generated data are no longer considered static, whose usefulness ends after the purpose of the collection is reached, they have become the raw material of the business, a vital economic resource, used to create a new form of economic value. Then comes the concept of “big data”. The objective of this research is to raise the discussion about the concept of big data, drawing from the current literature definitions that offer subsidies for the understanding of its real meaning and impact in the generation of useful ideas and goods and services of significant value. However, because it is a recent theme, the available literature is scarce. It is an applied purpose research with a descriptive purpose and uses the qualitative method of approach. It has by type of research the review of the literature for the theoretical basis, and also the study review of two cases through an exploratory research to collect the data to be analyzed. It seeks to confront the theory with the identified hypotheses and practices, to assess its adherence, arriving at informed conclusions, and to suggest future studies that may continue this line